Green Education Based on The Stage Learning Model to Build The Character of Students in The Nature School - Monica Widyaswari; Heryanto Susilo; Shobri Firman Susanto; Faliha Riasah (Universitas Negeri Padang, 2024)
The application of green education as a learning model can provide extensive knowledge and learning experience by understanding the environment around them so that students in the nature school can create positive characters as the next generation in preserving the surrounding nature. The role of educators is also expected to continue to be innovative and creative in creating learning media to increase response and interest in learning and build character at the first age of school. This study aims to find a way to build students' character through the stage learning model. The type of approach used in this research is a qualitative approach with case study methods. The location of this research is Sekolah Alam Pelopor Bandung. The research subjects were the institution's founders, educators, and guardians of students. The data collection techniques used were interviews, observation, and documentation studies. Followed by data analysis techniques using Miles and Huberman's analysis theory. Green education implemented in nature school through a stage learning model can build direct interaction between students and nature or the environment. In this way, it can create an attitude that fosters a love for the surrounding environment.